RUSSIAN-KYRGYZSTAN EXPEDITION ETHNOGRAPHIC RESEARCH IN THE ALTAI REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Over the past four years, ethnographers from Russia and Kyrgyzstan have been undertaking an expedition study of modern Turkic peoples within the framework of the Greater Altai project. During the expeditions of 2022 and 2024 in the Altai Republic, ethnographers studied the preserved traditions of Altaians and Telengites. The high-altitude and steppe character of the area of Southern Altai predetermined the development and preservation of cattle breeding among the Altaians and Telengites and related phenomena of material culture. The most stable phenomena of the traditional culture of the Altaians and Telengites, preserved to this day, are the traditional Altai dwelling, some elements of traditional costume and traditional food. Various religious and ideological practices related to nature and the veneration of various spirits play an important role in the life of modern Altaians. The indigenous population of Altai demonstrates high activity in preserving their traditional culture and its development. For this purpose, historical and ethnographic museums, guest houses are being created in rural areas, traditional crafts and folk games are being revived. At the same time, the ethnocultural heritage of the Altai Republic is in demand not only among Altaians and Telengites themselves, but also among tourists.
Keywords: Altai Republic, ethnographic expedition, Altaians, Telengites, traditional culture, revival of traditions, international cooperation